Heterosis studies for agronomic trait under different environmental conditions in sesame (Sesamum indicum L.) - Narendra Kumar, S. B. S. Tikka, Bhagirath Ram, M. C. Dagla (Electronic Journal of Plant Breeding, 2015)
An investigation was carried out to study extent of heterosis under four different environments for yield and its component traits in sesame. Diallel mating design excluding reciprocals was used to develop 28 F1 crosses from eight parents. Analysis of variance revealed highly significant differences among the parents vs hybrids was observed under four environments for all the characters, indicating the presence of significant amount of genetic variability for all traits under studied. Heterosis was worked out over mid parent, better parent and standard check, GT-2. For seed yield, crosses Pbtil-1 × AT-124, GT-10 × Pbtil-1 and GT-2 × PT-64 in E1, crosses GT-10 × TMV-3, GT-2 × PT-64 and GT-10 × Pbtil-1 in E2 and crosses TMV-3 × C-1013, TMV-3 × Pbtil-1 and GT-10 × Pbtil-1 in environment E3 having high per se performance along with significant mid parent, batter parent and standard heterosis. Hence, these crosses would be exploited for isolating transgressive segregants for seed yield and its component traits for genetic improvement in sesame.